(untitled) (Research, Society and Development, 2020)
Vegetation fires are complex processes that can have natural causes or be result of human activities. The effect of fire on an ecosystem varies according to its sensitivity, but the recurrence of fires can affect the environmental equilibrium and human health. Seeking to reduce the negative effects of fires, it is necessary to monitor their occurrence and understand their dynamics. In Brazil monitoring is carried out via satellites, which detect hot pixels. This process is performed by National Institute for Space Research (INPE), that provides data used in this work. In order to study the temporal variability of fires in the Amazon, Cerrado, Caatinga and Atlantic Forest biomes, this work uses the Horizontal Visibility Graph method that generates a complex network for each biome and, using topological measures, evaluates whether the series of hot pixels represent stochastic or chaotic process. The measures used are the Coefficient λ of the degree distribution, the Clustering Coefficient and the Average Path Length. The results showed that the topological properties of networks varied according to the number of hot pixels and the number of pixels per unit of area of biome. The fire dynamics presented the correlated stochastic process for Amazon, Cerrado and Atlantic Forest biomes and the chaotic process for the Caatinga biome.